Correlation of non stress test with fetal outcome in term pregnancy (37-42 Weeks) - Lohana, Richa U.; Khatri, Meena; Hariharan, Chella (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The main purpose of the various antepartum surveillance techniques is to detect fetal distress so as to prevent fetal death. Traditionally, obstetricians tended to classify pregnant women as “low” and “high” risk. Although many well-organized methods are available for managing the high-risk group, we need more efficient methods for identifying pregnant women in distress in the low-risk group. The idea of taking this study using NST as a tool for routine antepartum fetal surveillance is we will be trying to catch up those fetuses who might be at risk in womb and provide prompt intervention in otherwise considered normal pregnancies without any obvious high risk factor thus giving the best outcome in mothers. The objective of this study was to evaluate the correlation of the Non Stress Test with fetal outcome in pregnancies from 37-42 weeks of gestation. Methods: This was a prospective longitudinal study at Acharya Vinoba Bhave Rural Hospital Sawangi (Meghe) Wardha and Dept. of Obstetrics and Gynaecology Unit from August 2011- July 2013. This study included 100 normal pregnant mothers from 37 weeks to 42 weeks who were subjected to NST for 20 minutes. Results: The incidence of reactive test was 85% and that of Non reactive NST was 15% .As the gestational age advances the incidence of NR NST is more. Postdatism (gestation >40 weeks) is found to be an important factor for NR NST. Mode of delivery was related to results of Non stress Test in terms of maximum vaginal delivery in Reactive groups, Operative deliveries which occurred in the Reactive groups were also due to indications other than fetal distress. Caesarean section rate is slightly higher in non reactive NST. The individual parameters of poor fetal outcome like meconium stained liquor, Apgar score <7 at 5 minutes had increased incidences in the non reactive group. Conclusion: Routine electronic monitoring is accepted in high risk women, but normal pregnancies too require some reliable objective assessment to optimize the outcome. This study suggests that the NST was found to be a good predictor of the healthy foetus even in normal pregnancies between 37-42 weeks of gestation and the probability of an adverse outcome such as meconium-staining of liquor and poor Apgar score increases with a non reactive strip. However large randomized controlled trials are necessary to assess normal pregnancies to incorporate NST to monitor normal pregnancies.